Design and Optimization of a New Anti-reflux Biliary Stent With Retractable Bionic Valve Based on Fluid-Structure Interaction Analysis - Su, Yushan; Xiang, Zhongxia; Song, Xiaofei; Zheng, Shuxian; Xu, Xinsheng (Frontiers in Bioengineering and Biotechnology, 2022)
Duodenal biliary reflux has been a challenging common problem which could cause dreadful complications after biliary stent implantation. A novel anti-reflux biliary stent with a retractable bionic valve was proposed according to the concertina motion characteristics of annelids. A 2D equivalent fluid-structure interaction (FSI) model based on the axial section was established to analyze and evaluate the mechanical performances of the anti-reflux biliary stent. Based on this model, four key parameters (initial shear modulus of material, thickness, pitch, and width) were selected to investigate the influence of design parameters on anti-reflux performance via an orthogonal design to optimize the stent. The results of FSI analysis showed that the retrograde closure ratio of the retractable valve primarily depended on initial shear modulus of material (p < 0.05) but not mainly depended on the thickness, pitch, and width of the valve (p > 0.05). The optimal structure of the valve was finally proposed with a high retrograde closing ratio of 95.89%. The finite element model revealed that the optimized anti-reflux stent possessed improved radial mechanical performance and nearly equal flexibility compared with the ordinary stent without a valve. Both the FSI model and experimental measurement indicated that the newly designed stent had superior anti-reflux performance, effectively preventing the duodenobiliary reflux while enabling the bile to pass smoothly. In addition, the developed 2D equivalent FSI model provides tremendous significance for resolving the fluid-structure coupled problem of evolution solid with large deformation and markedly shortens the calculation time.